Modelling of Vapour-Gas Bubble Oscillation Using Linear Wave Equation - Al-Asady, Abbas Z. (Basrah Journal for Engineering Sciences, 2006)
By using linear wave equation a new model of bubble dynamics in acoustic field is constructed including effects of thermal conduction both inside and outside a bubble, and non-equilibrium evaporation and condensation of water vapour at bubble wall. The liquid temperature at bubble wall is numerically calculated by solving the heat conduction equation (without assuming a profile of liquid temperature). It is including effect of the latent heat of non-equilibrium evaporation and condensation at bubble wall. It is concluded that the liquid temperature increases to the same order of magnitude with that of the maximum temperature attained in the bubble at strong collapses. It is caused by the latent heat of intense vapour condensation and by the thermal conduction from the heated interior of the bubble to the surrounding liquid. The intense vapour condensation takes place at strong collapses because the pressure inside the bubble increases. The comparison is given between the calculated result and the experimental data of radius-time curve for one acoustic cycle. The calculated result fits well with the experimental data.